2021
DOI: 10.3389/fpsyg.2021.708375
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Double Empathy Problem Within Pairs of Autistic and Non-autistic Adults Through the Contemplation of Serious Literature

Abstract: Recent research based on the needs of the autistic community has explored the frequent social misunderstandings that arise between autistic and non-autistic people, known as the double empathy problem. Double empathy understandings require both groups to respect neurodiversity by focussing on individuality across groups. This study aimed to explore how literature, through its ability to uncover nuanced emotional response differences between readers, could facilitate double empathy understandings within pairs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 60 publications
(122 reference statements)
1
29
1
Order By: Relevance
“…In this way, literature may therefore be able to move non-autistic participants away from assumptions of pre-set mutuality and social norms (Milton, 2012;Chown, 2014) toward understanding the processes behind the Othering of neurodivergent individuals. Therefore, present findings indicate a potential for literature to promote double empathy understandings between autistic and non-autistic individuals, as shown in Chapple et al (2021b), through a move away from assumptions of mutuality and pre-set social norms.…”
Section: Double Empathy Implicationsmentioning
confidence: 63%
See 4 more Smart Citations
“…In this way, literature may therefore be able to move non-autistic participants away from assumptions of pre-set mutuality and social norms (Milton, 2012;Chown, 2014) toward understanding the processes behind the Othering of neurodivergent individuals. Therefore, present findings indicate a potential for literature to promote double empathy understandings between autistic and non-autistic individuals, as shown in Chapple et al (2021b), through a move away from assumptions of mutuality and pre-set social norms.…”
Section: Double Empathy Implicationsmentioning
confidence: 63%
“…Specifically, it is suggested that autistic individuals are more likely to take time in developing common ground and understanding different Others as a result of being more experienced in navigating a lack of mutuality (Milton, 2012 , 2020 ; Chown, 2014 ). In this way, autistic individuals may be more likely to work to sensitively and empathically overcome socio-communicative breakdowns rather than drawing quick conclusions based upon assumed pre-existing mutuality (Milton, 2012 ; Chown, 2014 ; DeBrabander et al, 2019 ; Chapple et al, 2021b ). Autistic writer Joanne Limburg ( 2021 ) expands upon this assumption by arguing that dehumanised individuals, such as those who are autistic, are forced to think about the ways in which modern society is constructed, giving them deeper understandings of the social world.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations